Time-series spectroscopy and photometry of the pulsating subdwarf B star PG 1219+534 (KY UMa) - Reed, M. D.; Eggen, J. R.; Harms, S. L.; Telting, J. H.; Ostensen, R. H.; Toole, S. J. O'; Terndrup, D. M.; Zhou, A. -Y.; Kienenberger, R. L.; Heber, Ulrich (Astronomy & Astrophysics, 2009)
Aims. We present observations and analysis of time-series spectroscopy and photometry of the pulsating subdwarf B star PG 1219+534 (KY UMa). Subdwarf B stars are blue horizontal branch stars that have shed most of their hydrogen envelopes. Pulsating subdwarf B stars allow a probe into this interesting phase of evolution.Methods. Low-resolution spectra were obtained at the Nordic Optical Telescope and Kitt Peak National Observatory, and photometric observations were obtained at MDM and Baker observatories in 2006. We extracted radial velocity and equivalent width variations from several Balmer and He I lines in individual spectra. The pulsation frequencies were separated via phase binning to detect line-profile variations in Balmer and helium lines, which were subsequently matched to atmospheric models to infer effective temperature and gravity changes throughout the pulsation cycle.Results. From the photometry we recovered the four previously observed frequencies and detected a new fifth frequency. From the spectra we directly measured radial velocity and equivalent width variations for the four main frequencies and from atmospheric models. We successfully inferred temperature and gravity changes for these four frequencies. We compared amplitude ratios and phase differences of these quantities and searched for outliers that could be identified as high-degree modes. These are the first such measurements for a "normal" amplitude pulsating subdwarf B star, indicating that spectroscopic studies can benefit the majority of pulsating subdwarf B stars.
Keywords: techniques: radial velocities; stars: subdwarfs; stars: variables: general; techniques: spectroscopic; stars: individual: PG 1219+534